PENERAPAN ARTIFICIAL NEURAL NETWORK PADA PROTOTYPING SISTEM MONITORING KUALITAS AIR DI KOTA BALIKPAPAN UNTUK MENDUKUNG BALIKPAPAN SEBAGAI SMART CITY - Dwi Arief Prambudi; Nia Febrianti (Universitas Palangka Raya, 2022)
Water quality plays an important role in the process of processing into clean water. Several parameters that support water quality monitoring are pH, temperature, TSS, BOD and DO. Water quality needs to be monitored regularly to find out whether the parameters have exceeded the quality standard or not, based on Government Regulation no. 22 of 2021 concerning the Implementation of Environmental Protection and Management in Appendix VI regarding the National Water Quality Standard. A water quality monitoring system is urgently needed to determine the feasibility of the consumption water. An artificial neural network is a neural network configured for a specific application, such as pattern recognition or data classification, and then refined through a learning process. This study aims to determine water quality through a quality index monitoring system and can predict water quality in the future in that place, so that the benefits that will be felt by residents are to become more aware and become more concerned about the environment, especially water is a basic or primary need. in everyday life. The stages of the research method include starting with a literature study and then a field survey followed by data collection on the water quality of the Manggar reservoir in Balikpapan, the raw data that has been obtained and then processed which is continued with data processing based on the Backpropagation method. After that, the system design can be carried out which is then continued with the system creation. The results of the study can be used as a basis and reference for follow-up on information systems on the water quality of the Manggar reservoir in Balikpapan City.